Comparison of Creep Life Assessment between Tin-Based Lead-Free Solders and Lead Solders - Kenji Monden (The Minerals, Metals and Materials Society, 2012)
"The creep properties of tin-based lead-free solders Sn3.0AgO.5Cu and SnO.7CuO.1Ni and lead solders 10Sn90Pb and 50Sn50Pb were investigated at temperatures between 298 K and 398 K. The creep-rupture time decreases with increasing initial stress and temperature. The analysis of the solder creep curves uses the Omega method. The creep rate E is expressed by following formula: 1n ? = 1n ?0 + O?, where ?0 and O are experimentally determined. The parameter Eo increases with increasing initial stress and temperature. The activation energy for ?0 is 108 kJ/mol for Sn3.0Ag0.5Cu and 85 kJ/mol for SnO.7CuO.INi. These energies suggest that the lattice diffusion of tin is dominant. The energy of 1OSn90Pb is 37 kJ/mol and that of 50Sn50Pb is 67 kJ/mol. The creep-rupture time is calculated using the parameters, ?0 and O. The calculated creep-rupture time is in good agreement with the measured creep-rupture time.IntroductionLead-free solders are replacing traditional tin-lead solders as part of a major trend toward protecting the earth's environment. However, tin-lead solders are currently needed for a high temperature range. Since creep is the main deformation mechanism in solder joints, understanding a constitutive model for creep and examining creep data for solders are important for reliability analysis of solder joints. A steady-state creep equation is generally used for solders [1,2], and it supposes that the secondary-, or minimum-, creep rate occupies the entire creep life. However, secondary creep accounts for only about 15 % to 40 % of the entire creep life for solders. Thus, the equation may not represent the entire creep life."